Performance evaluation of trommel screens: A case study of a municipal solid waste treatment plant - Dhananjay Singh Shyamal; Muntjeer Ali; Mandeep Singh; Absar Ahmad Kazmi (Waste Management Bulletin, 2024)
The efficient and effective operation of trommel screens is essential for the economic and environmental sustainability of mechanical biological treatment (MBT) based solid waste treatment plants. The present study evaluated the performance of four trommel screens (aperture sizes of 80, 32, 16, and 4 mm) being used at the MBT plant of the Municipal Corporation Karnal, India. The performance of trommel screens was evaluated at a fixed speed of rotation and inclination angle. For optimum performance, trommel screens must be operated at a particular range of feed rates with regular cleaning every four hours of operation. The organic recovery achieved by 80 mm and 32 mm aperture size trommel screen was 26.95 % and 95.82 %. The organic quality improvement achieved by 80 mm and 32 mm trommel screens was 122.50 % and 108.89 %. The trommel screen's heating value improvement and energy recovery ranged from 70.68 % to 135.16 % and 28.27 % to 98.74 %, respectively. The oversized fractions of trommel screens of opening sizes 80 mm and 32 mm meet the fuel specification prescribed by the Indian Solid Waste Management Rules 2016. The trommel screen's Specific Energy Consumption (SEC) ranged from 0.63 kWh/tonne to 5.66 kWh/tonne. The learnings and outcomes of this study are helpful for designers, policymakers, operators of solid waste treatment plants, and researchers.